Konsep Perancangan Interior Ruang Kelas Sekolah Minggu Gereja Pantekosta di Indonesia (GPdI) di Sidoarjo - Dodi Wondo, Viona Valentia Mariana Wibowo (Intra, 2013)
Sunday schoolis a place for spiritual growth and development of children. Spirituality as the foundation for the growth ofself-esteem, valuesanda sense of belongingis important in stilled since childhood, where the personality and behavior of individuals began tobe formed. Formation of personality and behavior are heavily influenced by the character of the physical environmentof his life. Therefore, it needs an environment that can effectively support the development of child spirituality. This study aims to find the concept of interior designing Gereja Pantekosta di Indonesia (GPdI) Sunday school classrooms in Sidoarjoâwhich can arouse the interest and support the spiritual development of children and reflectthe identity of the church organization. The concept will be used as the standard interior design of Sunday school classroom sthrough out GPdI in Sidoarjo.The study was conducted using the mixed research method. The result of participant observation, interviews, and questionnaires distributed to the sunday school teachers showed that the applied design concept of sundayschool classrooms could affect the spiritual development of children. Design concept was generated through the review of the organizationâs philosophy, liturgy, curriculum, and was oriented to the achievement of children spiritual and interest. From the outcome of the analysis and synthesis phase, thus obtained the design concept of GPdI sunday school classrooms interior design, the Unconditional Love.